Assessing the Impact of Excessive Gestational Weight Gain Among Women With Type 1 Diabetes on Overweight/Obesity in Their Adolescent and Young Adult Offspring: A Pilot Study - McWhorter, Ketrell L.; Bowers, Katherine; Dolan, Lawrence; Deka, Ranjan; Jackson, Chandra L.; Khoury, Jane C. (Frontiers in Endocrinology, 2018)
ABSTRACT Aims/hypothesis: We sought to determine the impact of intrauterine exposure to excessive gestational weight gain (GWG) on overweight/obesity in adolescent/young adult offspring of women with type 1 diabetes mellitus (TIDM). Methods: In 2008, a pilot study was conducted among 19 randomly-selected adolescent and adult offspring of mothers with TIDM who participated in the Diabetes in Pregnancy Program Project (DiP) between 1978 and 1995. Body mass index (BMI)-specific Institute of Medicine (IOM) guidelines for gestational weight gain (GWG) were defined as: 12.5-18.0 kilograms (kg) GWG; 11.5-16.0 kg GWG: 7.0-11.5 kg GWG; 5.0-9.0 kg GWG, for women classed as underweight, normal, overweight and obese according to pre-pregnancy BMI, respectively. Generalized estimating equations were used to estimate adjusted odds ratios (aOR, [95% confidence intervals, CI]) for overweight/obesity among offspring, related to IOM adherence, adjusting for pre-pregnancy BMI and mean maternal daily insulin units/kg body weight. Results: Mean age of offspring at follow-up was 20.3±3.3 years, 12(63%) were male, 4(21%) Black and 12(63%) overweight/obese. There were 9(82%) overweight/obese offspring among the 11 mothers who exceeded IOM guidelines for GWG compared with 3(38%) overweight/obese offspring among the 8 mothers with GWG within guidelines. Exceeding vs. adhering to IOM guidelines (OR=7.50, [95%CI: 0.92-61.0]) and GWG per kilogram (OR=1.39, [95%CI: 0.98-1.97]) were associated with offspring overweight/obesity at follow-up. Conclusions/interpretation: Our pilot study suggests potential long-term implications of excessive GWG on metabolic health in offspring of mothers with TIDM, warranting future research examining the health impact of gestational weight gain in this population.